Effects of soaking on physicochemical properties of four kinds of rice used in Huangjiu brewing. (January 2020) - Gong, Min; Zhou, Zhilei; Jin, Jianshun; Yu, Yongjian; Liu, Shuangping; Han, Xiao; Zhong, Fang; Mao, Jian
Abstract: Rice soaking is an important step in the Huangjiu brewing process. It affects the subsequent fermentation process and the quality of Huangjiu. However, the mechanism and physicochemical variation of rice soaking have been little studied. The physicochemical characteristics of japonica rice (JR), japonica glutinous rice (JGR), indica rice (IR) and indica glutinous rice (IGR) and their properties during the soaking process were studied and compared. The decreased pasting temperature of soaked rice indicated that they were easier to cook and gelatinize after soaking. The four kinds of rice and the soaked water showed different properties after soaking. During soaking, the total acids and amino nitrogen of the four kinds of rice increased slowly at first, then increased rapidly and finally became stable, while the reducing sugar content increased initially and then decreased. The soaking water of JGR showed the highest values of the physicochemical components, showing that it might be more profitable for further Huangjiu fermentation. Graphical abstract: Image 1 Highlights: Rice varieties have different soaking properties in the process of Huangjiu brewing. Soaking significantly affects the morphology and pasting properties of the rice. Total acid and amino nitrogen changes of soaked water in different rice varieties were consistent. The organic acids in the rice soaked water is mainly lactic acid and acetic acid. Japonica glutinous rice soaked water has the highest chemical components contents.